2022
DOI: 10.3389/fpls.2022.995429
|View full text |Cite
|
Sign up to set email alerts
|

Production of the SARS-CoV-2 Spike protein and its Receptor Binding Domain in plant cell suspension cultures

Abstract: The COVID-19 pandemic, caused by the worldwide spread of SARS-CoV-2, has prompted the scientific community to rapidly develop efficient and specific diagnostics and therapeutics. A number of avenues have been explored, including the manufacture of COVID-related proteins to be used as reagents for diagnostics or treatment. The production of RBD and Spike proteins was previously achieved in eukaryotic cells, mainly mammalian cell cultures, while the production in microbial systems has been unsuccessful until now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…To validate the effectiveness of the new transformation protocol, we selected a recombinant protein with a high impact in current worldwide research, the Receptor Binding Domain of the SARS-CoV-2 virus (Rebelo et al 2022 ). Other ongoing projects in the laboratory, in which we have used this new protocol, indicate that it is faster and simpler than previous methods (Rebelo et al in preparation; Vieira et al in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the effectiveness of the new transformation protocol, we selected a recombinant protein with a high impact in current worldwide research, the Receptor Binding Domain of the SARS-CoV-2 virus (Rebelo et al 2022 ). Other ongoing projects in the laboratory, in which we have used this new protocol, indicate that it is faster and simpler than previous methods (Rebelo et al in preparation; Vieira et al in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used the Receptor Binding Domain (RBD) of the SARS-CoV-2 coronavirus sequence codon optimized for Nicotiana tabacum and cloned into pTRA vector (pTRA_RBD) as described in Rebelo et al ( 2022 ). A. tumefaciens GV3101::PMP90RK containing pTRA_RBD was grown in YEB medium supplemented with 2 mM Mg 2 SO 4 , 50 mg/L Rifampicin and Kanamycin and 80 mg/L Carbenicillin (antibiotics from NZYTech).…”
Section: Methodsmentioning
confidence: 99%
“…In order to increase the immunogenicity of the antigen, RBD fused to flagellin of Salmonella typhimurium (Flg), known as mucosal adjuvant, was also transiently expressed with N. benthamiana using a self-replicating viral vector [ 76 ]. As an alternative to the transient expression platform, tobacco BY-2 and Medicago truncatula A17 cell suspension cultures were also used to stably express both full-length S protein and RBD [ 73 ]. The results showed that recombinant S protein and RBD could be secreted into the culture medium, which facilitated the subsequent purification and reduced the downstream processing costs.…”
Section: Plant Produced Biopharmaceuticals (Biologics) Against Sars-c...mentioning
confidence: 99%
“…Plant-based recombinant COVID-19 works have mostly been based on transient expression in Nicotiana benthamiana (see Table 1 and references therein). Only few studies involved the stable transformation of plant cell suspensions ( Daniell et al., 2022 ; Rebelo et al., 2022 ; Ferreira et al., 2023 ; Shen et al., 2023 ). Among the proteins reported, there are structural proteins such as the spike (S) protein or S subunits (S1 and S2), the receptor-binding domain (RBD), the nucleocapsid (NC), envelope (E), and membrane (M) viral proteins, and others such as angiotensin-converting enzyme 2 (ACE2) receptor and antibodies against domains of the spike protein (RBD and S1) and the nucleocapsid protein ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%